Nutrients and bioactive compounds in polycystic ovary syndrome: updated insights into effects and underlying mechanisms - Zhang, Yanli; Shi, Baichao; Tian, Yuan; Xu, Shujun; Chang, Hui (Frontiers in Nutrition, 2026)
Polycystic ovary syndrome (PCOS) is one of the most prevalent endocrine disorders affecting women of reproductive age. Its complex and heterogeneous clinical presentation has led international evidence-based guidelines to prioritize management strategies aimed at symptom control rather than cure, highlighting the need for novel therapeutic approaches. Women with PCOS frequently exhibit deficiencies in various vitamins and minerals, which are closely associated with the syndrome’s characteristic insulin resistance (IR) and endocrine disturbances. Consequently, nutritional supplementation may provide significant adjunctive benefits to conventional therapies. Accumulating evidence indicates that specific vitamins (e.g., E, K, D, B-8, B-9, B-12), minerals (e.g., selenium, chromium, zinc, calcium, magnesium), and other bioactive compounds (e.g., melatonin, ω-3 polyunsaturated fatty acids, coenzyme Q10, N-acetylcysteine) can ameliorate core PCOS manifestations. Their potential mechanisms involve regulating glucose and lipid metabolism, correcting hormonal imbalances, attenuating oxidative stress and chronic inflammation, and beneficially modulating gut microbiota composition. This narrative review synthesizes current evidence on the roles of these nutrients in PCOS, elucidates their potential mechanistic pathways, and discusses their clinical applicability, thereby providing insights for integrative management and future research directions.